DEVELOPMENT OF DIGITAL-BASED COVID-19 MITIGATION MEDIA (MISIMICOTIN) FOR ELEMENTARY SCHOOL - Eliya Rochmah; Erna Labudasari; Sri Sundhea Hastuti (Universitas Pendidikan Indonesia, 2022)
The objectives of the research are (1) the expansion of digital-based COVID-19 mitigation media literacy (Misimicotin) (2) The suitability of digital-based COVID-19 mitigation literacy media. The research method used for research is a combination of quantitative and qualitative (mixed methods) with research design and development (R D). Based on the research design that has been designed, the stages of R D research in this study are knowing the potential and problems, data collection, product design, design validation, design revision, and testing. Digital-based COVID-19 mitigation media literacy (Misimicotin) was created using Microsoft PowerPoint software which is then converted into an android application using Inspiring Suite 9 and Website 2 APK Builder. Based on the results of 3 expert validators, it was found that the media was quite feasible with an average score of 3.5, while the user response involving 30 elementary school-age respondents found that the average score of user responses was 89% agree and strongly agree so that user responses to learning media are at very good category.